Optimal planning to mitigate the impacts of roads on multiple species. Issue 1 (26th September 2018) - Polak, Tal; Nicholson, Emily; Grilo, Clara; Bennett, Joseph R.; Possingham, Hugh P.
Abstract: Common worldwide and encroaching on even the most remote locations, roads negatively affects wildlife through habitat loss, fragmentation and direct mortality. Reducing these effects requires mitigation, including wildlife crossing structures and fencing. However, mitigation measures are expensive and vary in their success level, especially when constructed to meet the needs of several species. Moreover, mitigation planning rarely considers the needs of multiple species. As funds are limited, deciding where and how to act for the greatest return on investment is crucial. Combining decision theory with a metapopulation model, we determined the most cost‐effective actions mitigating the effects of roads on multiple species. The model is illustrated with two sets of species with varying of life‐history traits, from a diversity of taxonomic groups. We tested the cost‐effectiveness of spatially explicit combinations of three management options for each road section: (a) no mitigation, (b) fences without wildlife crossings, and (c) fences combined with wildlife crossings. We explored the trade‐offs between each population's probability of persistence and total mitigation cost, first on a per‐species basis and then considering all species. We then tested the cost‐effectiveness of different planning strategies: (a) single species, (b) two types of focal species based on different life‐history traits, and (c) comprehensive multispecies planning. Planning for the needs of all species at the same time (multispecies strategy) maximizes the number of persisting species and provides the most robust and cost‐effective planning strategy, while single‐species strategies were found to be inefficient. However, basing decisions on the focal species with the largest home range can provide reasonably cost‐effective results, but should be considered only when there is not enough time or money to collect the necessary information to perform a multispecies analysis. Synthesis and applications . Our model can be adapted to most road mitigation problems. It illustrates that the needs of multiple species should be considered to plan a cost‐effective road mitigation system. However, when resources are limited to plan for all species, those with larger home ranges should be used as reasonable proxies for other species. Abstract : Our model can be adapted to most road mitigation problems. It illustrates that the needs of multiple species should be considered to plan a cost‐effective road mitigation system. However, when resources are limited to plan for all species, those with larger home ranges should be used as reasonable proxies for other species.